2015
DOI: 10.1016/j.cognition.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements reveal memory processes during similarity- and rule-based decision making

Abstract: Recent research suggests that when people retrieve information from memory they tend to fixate on the location where the information had appeared during encoding. We used this phenomenon to investigate if different information is activated in memory when people use a rule- versus a similarity-based decision strategy. In two studies, participants first memorized multiple pieces of information about various job candidates (exemplars). In subsequent test trials they judged the suitability of new candidates that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 78 publications
9
55
0
Order By: Relevance
“…This phenomenon in which individuals, while retrieving information from memory, gaze back at spatial locations previously associated with that information (during encoding) has been observed by other studies across different contexts and domains (Johansson & Johansson, 2014;Platzer, Bröder, & Heck, 2014;Renkewitz & Jahn, 2012;Scholz, Mehlhorn, & Krems, 2016;Scholz, von Helversen, & Rieskamp, 2015;Spivey & Geng, 2001). Collectively, these studies suggest that eye movements can be used as a measure of memory retrieval without the need for self-report responses.…”
Section: Eye-movement Measures Of Memory Retrievalsupporting
confidence: 74%
“…This phenomenon in which individuals, while retrieving information from memory, gaze back at spatial locations previously associated with that information (during encoding) has been observed by other studies across different contexts and domains (Johansson & Johansson, 2014;Platzer, Bröder, & Heck, 2014;Renkewitz & Jahn, 2012;Scholz, Mehlhorn, & Krems, 2016;Scholz, von Helversen, & Rieskamp, 2015;Spivey & Geng, 2001). Collectively, these studies suggest that eye movements can be used as a measure of memory retrieval without the need for self-report responses.…”
Section: Eye-movement Measures Of Memory Retrievalsupporting
confidence: 74%
“…For instance, participants who first encode an arrangement of objects and are later asked to recall aspects of that arrangement while looking at a blank screen will spontaneously execute eye movements "to nothing" on the blank screen, which largely correspond to the original object arrangement (e.g., Altman, 2004;Johansson & Johansson, 2014;Spivey & Geng, 2001). Research using such a blank-screen design has demonstrated that eye-movement patterns typical of various decision making strategies remain when decisionrelevant information is removed from the display and the decision is made strictly from memory (Jahn & Braatz, 2014;Renkewitz & Jahn, 2012;Scholz, von Helversen, & Rieskamp, 2015). In addition, compatibility of gaze positions between encoding and retrieval can increase the likelihood of successful remembering (Johansson & Johansson, 2014) and may trigger other associated memories (Platzer, Bröder, & Heck, 2014).…”
Section: Memory and Visually Available Informationmentioning
confidence: 99%
“…Observing such processes directly had not been done before, because methods were missing that could reveal the changing activation status of hypotheses over the course of a reasoning trial. We tested coherence maximization during diagnostic reasoning using memory indexing-a new method that is based on observing eye movements while participants solve memory-based, higher level cognitive tasks (Jahn & Braatz, 2014;Renkewitz & Jahn, 2010Scholz et al, 2015). This study provides evidence that eye movements reflect the tendency to maximize coherence in diagnostic reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…If eye movements can trace coherence maximization during sequential diagnostic reasoning, eye movements during later symptom presentations should reveal the integration of symptom information (see Renkewitz & Jahn, 2012;Jahn & Braatz, 2014;Scholz et al, 2015). For instance, if a later symptom supports two alternatives, gaze duration should be longer toward the leading hypothesis.…”
Section: Hypothesis 3: Integrated Probability Matchingmentioning
confidence: 99%
See 1 more Smart Citation